1996
DOI: 10.14507/epaa.v4n19.1996
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education in the United States

Abstract: School reform issues addressing inclusive education were investigated in this nationwide (United States) study. A total of 714 randomly selected middle school principals and teachers responded to concerns about inclusion, "degree of change needed in" and "importance of" collaborative strategies of teaching, perceived barriers to inclusion, and supportive activities and concepts for inclusive education. There was disagreement among teachers and principals regarding some aspects of inclusive education and collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Ecuador took part in such global educational policy to consider social inclusion as part of national policies. According to Tanner et al (1996), principals reported being highly involved in the planning process for students with disabilities in regular classrooms.…”
Section: Origin and Current Situation Of Inclusive Education In Ecuadormentioning
confidence: 99%
“…Ecuador took part in such global educational policy to consider social inclusion as part of national policies. According to Tanner et al (1996), principals reported being highly involved in the planning process for students with disabilities in regular classrooms.…”
Section: Origin and Current Situation Of Inclusive Education In Ecuadormentioning
confidence: 99%
“…Among those concerns are adapting to the curriculum and instructional practices and effectively synchronizing content for the special and general education classrooms (Ntshangase et al, 2008). Another area of concern identified as a barrier to full inclusion focuses on the high stake testing outcomes for students without disabilities in classes with students with disabilities (Tanner et al, 1996).…”
Section: Evolution Of Inclusive Education In the United Statesmentioning
confidence: 99%
“…One such area drawing serious concerns stems from the attitudes of educators (Fisher & Meyer, 2002; Kliewer & Biklen, 2001). For example, in a study conducted by Tanner et al (1996), the authors found disagreement between teachers and principals regarding inclusive education and collaborative strategies. The findings showed that principals and special education teachers had more positive attitudes regarding inclusion than teachers who taught in general classrooms.…”
Section: Evolution Of Inclusive Education In the United Statesmentioning
confidence: 99%